Gestión de logística y su incidencia en las ventas de la compañía indumadera de la ciudad de Quito, en el período 2014-2015 - Llamba Bonifa, Esteban Gustavo (2015)
This present research has as purpose carry out a logistics research and its incidence in sale in order to determine the causes in this area, therefore, It will perform the analysis of the main theoretical and methodological elements that form part of an effective management in order to organize the theme and develop a proposal focused to the improvement of the logistics management, reducing the incidence on sales, for mismanagement by the time of receipt, distribution, refund and inventory of them, thus it had to apply surveys to external and internal customers with which the company has to detect the causes of inadequate logistics management, and the results obtained shown that there is not a planning….